Bridging the research gap in conflict-affected countries: A multi-institutional study on medical students’ research involvement and barriers in Yemen - Mohamed Baklola; Naji Al-bawah; Mohammed Al-Shehari; Amira Yasmine Benmelouka; Amjed Al-Jahmi; Ahmed A. Khailah; Hend O. Al-Sabri; Khaled Badr; Saif Alaribi; Jafar A. Mohammed; Hadeel Alashwal; Mohammed Badi; et al. (PLoS ONE, 2026)
Background Undergraduate research engagement plays a pivotal role in promoting evidence-based medical practice, particularly in low-resource and conflict-affected settings such as Yemen. However, multiple structural and academic barriers often limit students’ ability to actively participate in research. This study aimed to assess medical students’ research knowledge, attitudes, participation, and perceived barriers in a multi-institutional setting in Yemen. Methods A cross-sectional survey was conducted among undergraduate medical students from ten universities in Yemen using a structured online questionnaire assessing research knowledge, attitudes, participation, and perceived barriers. Data were collected between April and July 2025. Statistical analyses included descriptive statistics, independent t-tests, one-way analysis of variance, and linear regression to identify factors associated with research knowledge and attitudes. Results A total of 1,387 students participated in the study, with a mean age of 23 years; 70.7% were male. Although most students (79.8%) agreed that research should be an integral part of medical education, only 20.5% reported having published a research paper, and 41.5% had never attempted to write one. The mean research knowledge score was low (2.8 out of 10), with no significant difference by gender. Fifth-year students demonstrated the highest knowledge scores (mean = 3.2, SD = 2.0; p = 0.003). Academic performance was a significant predictor of both research knowledge and attitudes ( p < 0.001). The most frequently reported barriers were insufficient training in research methods (81.0%), inadequate research facilities and resources (76.0%), limited research opportunities (74.2%), and insufficient faculty guidance (72.3%). Conclusion Participating medical students demonstrated generally positive attitudes toward research; however, their research knowledge and active involvement remained limited. Persistent institutional and structural barriers, including limited research training, mentorship, and infrastructure, may hinder meaningful research engagement. Strengthening research training and institutional support within undergraduate medical education may help improve research engagement in resource-limited and conflict-affected settings.